2003
DOI: 10.1007/s00441-003-0779-0
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages and dendritic cells in the rat meninges and choroid plexus: three-dimensional localisation by environmental scanning electron microscopy and confocal microscopy

Abstract: The present investigation provides novel information on the topographical distribution of macrophages and dendritic cells (DCs) in normal meninges and choroid plexus of the rat central nervous system (CNS). Whole-mounts of meninges and choroid plexus of Lewis rats were incubated with various anti-leucocyte monoclonal antibodies and either visualised with gold-conjugated secondary antibody followed by silver enhancement and subsequent examination by environmental scanning electron microscopy or by the use of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(109 citation statements)
references
References 42 publications
8
97
0
1
Order By: Relevance
“…Studies of brain show that DC are not found in immunologically quiescent parenchyma, but are recruited after the onset of inflammation (10). DC are found in all layers of the meninges, including the pia mater and the choroid plexus (63,64) of the CNS, and could be an important source of recruited APC. This localization of DC will lead to contamination of brain preparations with meningeal-derived DC, unless exceptional measures are taken in the dissection of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of brain show that DC are not found in immunologically quiescent parenchyma, but are recruited after the onset of inflammation (10). DC are found in all layers of the meninges, including the pia mater and the choroid plexus (63,64) of the CNS, and could be an important source of recruited APC. This localization of DC will lead to contamination of brain preparations with meningeal-derived DC, unless exceptional measures are taken in the dissection of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…22 Moreover, cells derived from the different shake-offs are known to have a comparable in vitro phenotype, based on the phagocytic ability, morphology, specific immunoreactivity, cytokine secretion, and LPS response. 35 However, there was still the possibility that our shake-offs also contained blood mononuclear cells that had been trapped in the vasculature, or dendritic/myeloid cells initially located in the perivascular or meningeal compartments, 1,2,36 and that the GM-CSF/ IL-4 -recruited micDCs derived from these cellular sources. To clarify this issue, we produced bone marrow chimeras by injecting hematopoietic stem cells of GFPtransgenic Lewis rats into irradiated wild-type Lewis rats.…”
Section: Cell Cultures Derived From Bone Marrow Chimeric Rats Reveal mentioning
confidence: 99%
“…1,2 Under pathological conditions like inflammation, 3 degeneration, 4 infection, 5 and ischemia, 6 these cells increase in numbers, mostly by immigration from the peripheral immune system, but also by differentiation of parenchymal microglial cells. 6,7 While there is ample information available about the recruitment of dendritic cells to the CNS and about their possible contribution to the exacerbation [7][8][9] or attenuation 6 of local immune responses, little is known about the exit of DCs from the CNS.…”
mentioning
confidence: 99%
“…This point is of importance because DCs are absent from normal CNS parenchyma, 7 but they can be detected in CSF and in compartments associated with CSF circulation or production, including meninges and choroid plexuses. [8][9][10] Moreover, under neuroinflammatory conditions, DCs accumulate in the CSF 11,12 as well as in perivascular spaces, 13,14 anatomic compartments draining into the CSF. These findings, along with others, suggest that the CSF may be a major transport route for DCs circulating in the CNS and migrating either from CSF to CNS parenchyma or from CSF to the lymphoid organs.…”
Section: Introductionmentioning
confidence: 99%